Variables of the action-angle type on symplectic manifolds stratified by coisotropic tori - Parasyuk, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A symplectic manifold is considered under the assumption that a smooth symplectic action of a commutative Lie group with compact coisotropic orbits is defined on it. The problem of existence of variables of the action-angle type is investigated with a view to giving a detailed description of flows in Hamiltonian systems with invariant Hamiltonians. We introduce the notion of a nonresonance symplectic structure for which the problem of recognition of resonance and nonresonance tori is solved.